The problem of capturing marginality in model reductions of turbulence. (1st May 2023) - Gillot, C; Dif-Pradalier, G; Sarazin, Y; Bourdelle, C; Bañón Navarro, A; Camenen, Y; Citrin, J; Di Siena, A; Garbet, X; Ghendrih, Ph; Grandgirard, V; Manas, P; et al.
Abstract: Reduced quasilinear and nonlinear (gradient-driven) models with scale separations, commonly used to interpret experiments and to forecast turbulent transport levels in magnetised plasmas, are tested against nonlinear models without scale separations (flux-driven). Two distinct regimes of turbulence—either above threshold or near marginal stability—are investigated with Boltzmann electrons. The success of reduced models hinges in particular on the reproduction of nonlinear fluxes. Good agreement between models is found above threshold, whilst reduced models significantly underpredict fluxes near marginality, overlooking mesoscale flow organisation and turbulence self-advection. Constructive prescriptions whereby to improve reduced models are discussed.